Black Pepper Price and its Determinants: A Panel Data Analysis using different Estimators - KORAH, GEEMON; KUMAR, DR. S MOHAN (The journal of contemporary issues in business and government, 2021)
The study intends to identify the linkages between black pepper price and its determinants. Area harvested, production and yield of pepper are taken as the determinants of black pepper price in this study. The research is designed as a panel data analysis, using different estimators like random effect, fixed effect, mixed effect, generalised method of moments (GMM 1991 and GMM 1998) and panel quantile regression. Research design adopted is descriptive in nature. Analysis was done based on panel data of five pepper producing countries for a period of 51 years from 1969 to 2019. The study revealed that area and production are significant predictors of pepper price in all the countries, while yield cannot be considered as a significant determinant of pepper price across countries.